Fotodestruição do benzeno em ambientes interestelares - Neves, Rosicler da Silva (2007)
The abundance of interstellar molecules depends on their dissociation and destruction rate, and those depend on the photodissociation cross section which is function of the photon energy. We had experimentally study photoionization and photodissociation processes of the benzene (C6H6), and the deuterated benzene (C6D6). Benzene is an essential intermediate in the formation pathways of polycyclic aromatic hydrocarbons (PAHs), which are thought to be responsible for unidentified infrared bands (UIR), observed in differents astronomical environments. The measurements were taken at the Brazilian Synchrotron Light Laboratory (LNLS), using soft X-ray and UV photons. The experimental set-up consists of a high vacuum chamber with a Time-Of-Flight Mass Spectrometer (TOF-MS). Kinetic energy distributions, abundances for each ionic fragment and dissociative and non-dissociative photoionization cross sections were determined by using PhotoElectron PhotoIon Coincidence techniques. We have observed that C6H6 is extremely resistant to UV photons, confirming that PAHs absorb the UV photons and after some internal energetic rearrangements, they can emit in the IR range. However, this molecule is destroyed by soft X-rays photons producing several ionic fragments. We also observed that C6D6 is more resistant than benzene. Stable doubly-charged species were observed. From the photodissociation and cross sections we have determined the photodissociation rate and the half-life of C6H6 and C6D6 in differents astrophysical environments.